2018
DOI: 10.11158/saa.23.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the main phytophagous and predatory mites associated with rubber tree plantations in the State of Bahia, Brazil

Abstract: Rubber trees, Hevea brasiliensis, are the main source of latex in the world, being cultivated in several states in Brazil. Calacarus heveae Feres and Tenuipalpus heveae Baker are considered the main pest mites of this crop. In this study, we evaluated the population dynamics of these two phytophagous species and of the most common predatory species during a one-year period on crops of rubber tree clones FDR 5788, CDC 312 and PMB 01, located in Igrapiúna, State of Bahia, northeastern Brazil. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…In this study, the number of predator mites was significantly correlated with the number of phytophagous mites, whereas the environmental variables tested were not correlated with mite quantity. The concentration of chemical components in the host plants may affect the population levels of herbivorous arthropods (Awmack & Leather, 2002), as well as the susceptibility of different clones of plants (Castro, Nuvoloni, & Feres, 2018). Castro et al (2018) suggested that climatic factors played a secondary role in the population levels of phytophagous mites Calacarus heveae Feres (Acari: Eriophyidae) and Tenuipalpus heveae Baker (Acari: Tenuipalpidae), considering that the population dynamics of these species are determined mainly by plant physiology owing to small variations in relative humidity and temperature and evenly distributed rainfall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the number of predator mites was significantly correlated with the number of phytophagous mites, whereas the environmental variables tested were not correlated with mite quantity. The concentration of chemical components in the host plants may affect the population levels of herbivorous arthropods (Awmack & Leather, 2002), as well as the susceptibility of different clones of plants (Castro, Nuvoloni, & Feres, 2018). Castro et al (2018) suggested that climatic factors played a secondary role in the population levels of phytophagous mites Calacarus heveae Feres (Acari: Eriophyidae) and Tenuipalpus heveae Baker (Acari: Tenuipalpidae), considering that the population dynamics of these species are determined mainly by plant physiology owing to small variations in relative humidity and temperature and evenly distributed rainfall.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of chemical components in the host plants may affect the population levels of herbivorous arthropods (Awmack & Leather, 2002), as well as the susceptibility of different clones of plants (Castro, Nuvoloni, & Feres, 2018). Castro et al (2018) suggested that climatic factors played a secondary role in the population levels of phytophagous mites Calacarus heveae Feres (Acari: Eriophyidae) and Tenuipalpus heveae Baker (Acari: Tenuipalpidae), considering that the population dynamics of these species are determined mainly by plant physiology owing to small variations in relative humidity and temperature and evenly distributed rainfall. Reis et al (2008) did not find significant correlations between the population levels of Aceria guerreronis Keifer (Acari: Eriophyidae) and phytoseiids evaluated with abiotic factors (temperature, humidity, and precipitation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent that Acari is a functional group of phytophagous organisms. This indicates that its abundance in agricultural areas can be explained by the quantity and quality of the biomass available in such systems (CASTRO et al, 2018). In addition, the application of agricultural inputs such as agrochemicals eliminates other functional groups that live on the soil cover and regulate the community of Acari (CARVALHO et al, 2018) that lives among the vegetal residues in the area cultivated with soybean crops.…”
Section: Resultsmentioning
confidence: 99%
“…This contributes to an increase in the quantity and quality of food available to the invertebrate fauna of the soil and benefits the abundance and ecology of the epigeal fauna (BATISTA et al, 2014;MUELLER et al, 2015;BEDANO et al, 2016;FRANCO et al, 2016, RODRIGUES et al, 2016FARIAS;HERNADEZ, 2017;ČUCHTA et al, 2019). However, Assis et al (2017), Castro et al (2018), Carvalho et al (2018) and Čuchta et al (2019) described that the inadequate occupation of soil and crops contributes to an imbalance in the dynamics of the taxonomic groups that compose the epigeal fauna.…”
Section: Introductionmentioning
confidence: 99%